Doses de composto orgânico na produtividade e acúmulo de macronutrientes em chicória - Lanna, Natália B. L. [UNESP]; Silva, Priscilla Nátaly L. [UNESP]; Colombari, Lidiane F. [UNESP]; Freitas-Nakada, Pâmela G. [UNESP]; Ismael, Antonio [UNESP]; Cardoso, Inácio [UNESP] (FapUNIFESP (SciELO), 2017)
The authors evaluated the effects of doses of organic compost on the production and accumulation of macronutrients in endive plants in two areas with different fertility levels. The experiments were carried out at Fazenda Experimental São Manuel, located in the municipality of São Manuel, São Paulo State, Brazil. The study was carried out in a completely randomized design with seven treatments, six doses of organic compost (0, 35, 70, 105, 140 and 175 t/ha) and one additional treatment with inorganic fertilizer (N-P-K 4-14-8) and four replicates. In both areas, when the dose of organic compost was increased, the authors noticed a linear increase in fresh matter weight, number of leaves and plant height. In high-fertility area, compared to control (dose 0), using the highest dose (175 t/ha), the authors observed an increase of 280, 58 and 101% in fresh matter weight, number of leaves and plant height, respectively. For dry weight, we observed a linear increase in low fertility area and quadratic effect in high fertility area, with maximum estimated dry matter of 22.26 g applying 144 t/ha of organic compost. The nutrient accumulation was proportional to dry matter, with a linear increase in low fertility area and quadratic effect in high fertility area. The decreasing order of accumulated nutrients was K>N>Ca>P>S>Mg, with the highest values, in high fertility area, of 1,269, 471, 185, 91, 53 and 35 mg/ plant, respectively, for doses varying from 121 to 158 t/ha.
Doses of organic compost on yield and accumulation of macronutrients on endive
Keywords: Cichorium endivia; Plant nutrition; Soil fertility